Maqashid Sharia Analysis of Change From Customers for Donation: a Case Study in Fajar Toserba, Jalaksana District - Alfan Syafi'i; Ega Kusuma Dewi (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2021)
The Qur'an and Islamic legal literature do not mention the word Islamic law as one of the terms in the Qur'an is the word syarî'ah, fiqh, Allah's law, and the same root with it. The term Islamic law is a translation of Islamic Law in western literature. If traced to its roots, then the meaning of Islamic law is